Cardiac mitochondrial nitric oxide: a regulator of heart rate? - Fellet, Andrea L. (2008)
Alterations in autonomic control and myocardial nitric-oxide (NO) production are likely linked to the development and progression of heart dysfunction. By focusing on heart rate, the complexity of the actions of NO at distinct levels throughout the autonomic nervous system and its relationship with other regulators can be demonstrated. Given the multiple and opposing actions of NO on cardiac control, it is difficult to interpret a response after a global intervention in the NO system. The diversity of intracellular pathways activated by NO, and their differing sensitivities to different levels of NO, might account for some aspects of reported specific but opposite effects. We discuss factors that might contribute to this diversity of actions. A proper elucidation of the effects of NO on metabolic pathways and on energy generation could lead to novel therapeutic strategies aimed at the early treatment of heart dysfunction.